Proactive Description for Useful Applications: Researching Language Options for Better Translation Practice? - Rabadán, Rosa (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe initial assumption for this inquiry is that producing useful applications is part of the research process, and that it is the duty of the researcher to ‘transfer’ the knowledge gained in basic, descriptive research to ‘know-how’ packages to be used by other professionals/ in other activities. This paper illustrates a contrastive corpus-based research procedure using a case study: the translation of English ‘Past Progressive’ forms into Spanish. The results are presented as an inventory of ‘descriptively prescriptive’ translation solutions to be used by practitioners and translation trainers. They can also be used in the area of evaluation, as an objective filter to assess language performance in translations or as a descriptive tertium comparationis for the interpretation of translational shifts obtained from work done (exclusively) with parallel corpora (STEng- TTSp).